New maps representing the historical and recent distribution of the African species of rhinoceros: Diceros bicornis, Ceratotherium simum and Ceratotherium cottoni - Kees Rookmaaker; Pierre-Olivier Antoine (Pachyderm)
The paper presents new and updated maps showing the historical and current range of the black, white and Nile rhinoceros. Distribution of the species is based on written and iconographical records, as well as museum specimens. The historical range reflects the situation from ad 1500 onwards (or the last part of the Holocene). The current range is divided into original and introduced populations.